Fraksinasi Sari Kulit Buah Pisang Kepok (Musa acuminata) Mentah Tua dan Evaluasi Aktivitas Antibakteri terhadap Pertumbuhan Bakteri Propionibacterium acnes - Azhari, Yusron; Azim, Muhlisun; Gemantari, Baiq Maylinda (Sinteza, 2023)
Acne vulgaris is a skin condition performed the acne due to bacterial activity that infects the skin. Acne problems are often the cause of a person that decrease in self-confidence. One of the most common acne-causing bacteria is Propionibacterium acnes. P.acnes is a gram-positive bacterium with its morphological, shape, properties and composition classified in the group of corynebacteria, but this type of bacteria is not toxigenic or bacteria that does not produce toxic substances (toxic). One of the materials that can be used for acne medication is banana peel. Banana peels are residual waste products from domestic industrial production. The waste of Banana peels have potential as an antibacterial. They contain secondary metabolites such as phenolics, quinones and flavonoids which can act as antibacterials. The purpose of this study was to examine the antibacterial activity of raw kepok banana (Musa acuminata) peel extract against Propionibacterium acne bacteria as a cause of acne. Antibacterial activity test in this study was carried out using the well diffusion method to see how the antibacterial effect of raw kepok banana peel (Musa acuminata) had on the growth of Propionibacterium acnes bacteria. Kepok banana peel extracts were fractionated with hexane, ethyl acetate and water. The results of the antibacterial activity test for the three fractions showed that the water fraction of kepok banana peel extract represented the best inhibition zone of 10.02 ± 0.05 mm, 11.28 ± 0.13 mm, 12.38 ± 0.02 mm and 16.97 ± 0.36 with a strong category at successive concentrations of 20%, 40%, 60% and 80%.